Lazer, mulheres trans e unidade prisional: um estudo sobre as práticas de lazer na penitenciária professor Jason Soares Albergaria - Felipe Fonseca Oliveira Rodrigues (2022)
This paper investigates the leisure experiences of trans women in the Professor Jason Soares Albergaria penitentiary, a prison unit located in the municipality of São Joaquim de Bicas, in the Metropolitan Region of Belo Horizonte, Minas Gerais-BR. It is the first prison unit in Brazil fully intended for self-declared LGBT+ detainees, and one of the existing pavilions there has been reserved for transgender women. The aim of the work was to describe and analyze the possibilities of leisure by trans women in a context of deprivation of liberty, how the activities are carried out and organized, and how the spaces are appropriated by them. It is based on the combination of bibliographic and field research, carried out in the prison unit, with the use of direct observation, an opportunity in which it was possible to get to know the spaces and visualize the social interactions that occurred there. After that, we also carried out focus groups with the target audience, trying to extract from the conversations the meanings they attribute to leisure, their demands in this area, impacts, and needs. Despite leisure being a fundamental human right, protected in international diplomas and guaranteed in the Brazilian legal system, the research shows that there is no perception of leisure as a right in a prison unit, seen rather as a benefit, a perk. The government is not responsible for providing resources for leisure activities, and nowadays there are occasional initiatives financed by family members and volunteer agents. Among these initiatives, there is the Beauty Parlor, a space that they claim for the care of their aesthetics and for the increase of their self-esteem - leisure that touches them intimately, an environment of sociability and translated into a mechanism of personal strengthening. We discuss how the right to sunbathing has been made possible, the social isolation and the difficulties in receiving social visits, as well as highlighting the activities visualized inside some cells, such as reading, writing, watching television or radio, practicing handicrafts or drawing. It is noteworthy that certain activities, by involving physical or mental effort, are sometimes perceived as leisure time, and sometimes claimed as work time. Moreover, it is highlighted how social markers (gender, poverty, race, health) interfere in the access to leisure inside prison and how other basic needs (social name, gender-appropriate clothing, absence of hormonal procedures, care, and food) can dialogue in a process of generating well-being. This paper, in sum, goes through the different spaces occupied by trans women deprived of freedom in pavilion 1 of Jason Penitentiary and seeks to describe their leisure possibilities.